Obsessionen und gesichte : Kunst aus Flandern - Buyck, Jean F.; Dückers, Alexander; Geirlandt, Karel; Meewis, Wim; Mertens, Phil; Pauwels, Henri (Berlin : Haus am Waldsee, 1985)
Ensor, James ; Cox, Jan ; Bervoets, Fred ; Roobjee, Pjeroo ; Gentils, Vic ; Van Hoeydonck, Paul
Obessionen und gesichte, Kunst aus Flandern, Haus am Waldsee, Berlin, 26.10 - 15.12.1985
boek